2008
DOI: 10.4319/lo.2008.53.6.2573
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of nitrogen removal from headwater streams in an agricultural watershed, northeast Ohio, U.S.A

Abstract: The objective of this project was to assess in-stream nitrogen removal capacity in a fragmented agricultural landscape and to compare removal capacities in streams with agricultural or residential (hereafter referred to as agricultural streams) and forested riparian land use. We also identified what stream characteristics control nitrogen removal in these systems. We examined paired reaches (one agricultural and one forested reach) along five headwater streams in an agricultural watershed (Upper Sugar Creek Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…The seasonal differences in denitrification rates were not likely due to bulk sediment characteristics (% organic matter, % silt, bulk density) or nitrate and dissolved organic carbon concentrations of ground water used in the incubations, as the magnitude of these variables did not vary among seasons. Other investigators have shown seasonal variation in denitrification rates in stream sediments, including higher rates during the summer when comparisons were made within substratum or habitat types (Richardson et al, 2004;Schaller et al, 2004;Arango et al, 2007;Herrman et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The seasonal differences in denitrification rates were not likely due to bulk sediment characteristics (% organic matter, % silt, bulk density) or nitrate and dissolved organic carbon concentrations of ground water used in the incubations, as the magnitude of these variables did not vary among seasons. Other investigators have shown seasonal variation in denitrification rates in stream sediments, including higher rates during the summer when comparisons were made within substratum or habitat types (Richardson et al, 2004;Schaller et al, 2004;Arango et al, 2007;Herrman et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Many studies of nitrogen uptake and removal in streams, including those based on whole‐stream injections [ Mulholland et al , 2008], sediment cores [ Herrman et al , 2008], and nitrogen retention at the network scale [ Wollheim et al , 2008] have not considered nitrogen processing in deep sediments. However, as our results have shown deep stream sediments, like riparian zones [ Hedin et al , 1998], can be locations where oxic nitrate‐rich groundwater from upland areas encounters favorable redox conditions for reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen processing studies at reach scales are usually designed to measure nitrogen uptake or transformation in stream channels [ Mulholland et al , 2008; Heffernan et al , 2010] and those studies at smaller spatial scales typically emphasize shallow sediments. For example, most studies of denitrification in stream sediments only include denitrification measurements from surficial sediments (cores less than 5 cm deep) [ Arango et al , 2007; Herrman et al , 2008] (also see review in Stelzer et al [2011b]). In gaining streams groundwater often passes through substantial quantities of sediment before discharging to the stream.…”
Section: Introductionmentioning
confidence: 99%
“…Herrman et al, 2008;Nimick et al, 2011;Palmer-Felgate et al, 2008;Pellerin et al, 2012). Those studies that measure sub-daily instream NO 3 dynamics tend to be based on short-term monitoring schemes, spanning a few days or specific months (e.g.…”
Section: Introductionmentioning
confidence: 99%